Community Empowerment through Agricultural Commodity Processing Training as an Effort to Improve Community Welfare in Kerta Barat Village, East Java - R Amilia Destryana; Ismawati Ismawati; Rika Diananing Putri; Ratih Yuniastri (Journal of Community Practice and Social Welfare, 2021)
Kerta Barat Village in Dasuk District is one of several tomato and chili producing areas in Sumenep Regency. The economic potential of processed food production from agricultural commodities is considerable. This potential can be further increased by harvest abundance. Tomatoes and cayenne chillies are categorized as agricultural commodities with a shelf life and are difficult to store for long periods. The best solution to the overabundance of crop products is by processing these agricultural materials into processed products capable of extended periods of storage. Additionally, processed food products will add to the economic value of the commodity itself. This community service aims to empower the people of Kerta Barat Village by exploiting the potential of agricultural commodities through the processing of tomato sauce and cayenne chilli powder products. This activity was carried out through training and mentoring on the subject of food product processing of tomato sauce and cayenne chili powder. Knowledge and skill increase were seen to have followed this empowerment activity, namely partners can process tomato and cayenne chilly commodities into tomato sauce and cayenne chili powder products through the use of simple technology. A social impact was perceived where partners have become acquainted with agricultural commodity processing technology, namely for the process of drying and size reduction in the manufacturing of processed tomato and cayenne chili products. Additionally, the utilization of post-harvest technologies is crucial for the process of making produced commodities more useful and increase its economic value, which in turn can lead to welfare for the locals.